Evidence of the effect of wealth observed by criminals on the risk of becoming a victim of property crimes - Marcelo Justus; Ana Lúcia Kassouf (EconomiA, 2013)
The objective of this paper is to measure the effect of wealth on property victimization risk. Using data from two household victimization surveys conducted in S\~ao Paulo city and a measure of spending as a proxy for wealth observed by criminals, the conclusion was reached that wealth level is one of the determinants of victimization risk. This risk increases with this variable, but it reaches a maximum level from which it declines as wealth levels increase. – – O objetivo é mensurar o efeito da riqueza no risco de vitimizaç\~ao contra a propriedade. Utilizando dados de duas pesquisas domiciliares de vitimizaç\~ao realizadas na cidade de S\~ao Paulo, e uma medida de despesa realizada como proxy para a riqueza observada pelos criminosos, conclui-se que o nível de riqueza é um dos determinantes do risco de vitimizaç\~ao. O risco cresce com essa variável, mas atinge um ponto de máximo, a partir do qual se reduz para maior riqueza.
Keywords: C35; D69; 330; Violence; Victimization; Property crime